Coins from the Excavations at the "T-4" Site in Olbia - Kozlenko, R.O.; Sheiko, I.M.; Reuter, A. (Археологія і давня історія України, 2021)
Coins are published from the latest excavations at «T-4» sector, laid in 2018 in the Terrace City of Olbia. The presented numismatic material covers all the main chronological periods of the polis existence.